Pengaruh Pembiayaan Mudharabah dan Pembiayaan Musyarakah Terhadap Profitabilitas Bank Umum Syariah di Indonesia - Erlyna Damayanti; Sri Suartini; Isro’iyatul Mubarokah (ITB AAS INDONESIA Surakarta, 2021)
The purpose of this study was to analyze the effect of mudharabah financing and musyarakah financing on profitability of Islamic commercial banks in Indonesia for the 2017-2019 period. The research method used is descriptive research with a quantitative approach using secondary data as research material. Secondary data used are the quarterly financial reports of PT Bank Muamalat Indonesia, PT Bank BRI Syariah, and PT Bank Bukopin Syariah for the 2017-2019 period. The sampling method used was purposive sampling. The data analysis technique used the classical assumption test (normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test). After that to test the hypothesis (t statistical test, f statistical test, and the coefficient of determination), and multiple linear regression analysis. The results showed that both mudharabah and musyarakah financing had an influence on profitability (ROA). Furthermore, partially mudharabah financing has a positive and significant effect on profitability (ROA). Then for musharaka financing partially has a negative and significant effect on profitability (ROA).